Employment of ash derived from agricultural waste for sustainable cement replacement in flowing concrete - Rochmah, Nurul; Antariksa, Antariksa; Wisnumurti, Wisnumurti; Semedi, Bambang (Edelweiss Applied Science and Technology, 2025)
The increasing amounts of agricultural residues, including rice husks and sugarcane bagasse in Indonesia, present an escalating threat to environmental quality and public health if not managed properly. As reported by the Central Bureau of Statistics in 2024, rice husk waste has reached approximately 10.5 million tons, while sugarcane bagasse accounts for about 7.41 million tons. According to previous studies, ashes from sugarcane bagasse and rice husks in concrete can enhance certain mechanical properties while promoting eco-friendly construction practices. These ashes exhibit pozzolanic behavior, which makes them suitable for partially replacing cement, thus reducing the carbon footprint of concrete production. This study investigates alternative materials substituting a portion of cement with ashes derived from sugarcane bagasse and rice husks to determine how they contribute to the properties of flowing concrete, utilizing Sika-Viscocrete as a superplasticizer. The flowing concrete was evaluated based on its slump flow and absorption. In this investigation, the slump flow test was carried out following ASTM International [1] while the absorption test was executed according to SNI 03-6433-2000. The results showed that all slump flows met the standard requirements, with the minimum absorption value being 3.34% at a variation of 12.5% rice husk ash.